Study of heat transfer through micro-structured surfaces - Chin, Wei Hao (2016)
The phenomenon of film boiling is used in the experiment to study the thermo-physical properties of silicon chips. The heat transfer performance of a chip can be determined directly from the calculation of the critical heat flux of the liquid medium surrounding the chip, just as the boiling curve arrives at the film boiling zone. A silicon chip of dimensions 15x18mm is used as a starting control to be compared later on. The two liquids to be boiled are namely FC-72 and Ethanol. The tabulation of results will cease as soon as film boiling is achieved for both substrates. Once all readings have been conducted on the unmodified chip, 3 different types of enhanced chips will then be placed into the setup and the experiments will be carried out again with the above mentioned fluids. Each chip has a different microstructure in the form of very small and elongated pin-fins, which will in turn affect the critical heat flux of each component. This research aims to to evaluate the improvement of heat transfer performance and analyze the dependence of the dependence of the heat transfer on the height of micro pin-fins as a control parameter. A series of trial and error is done by varying the physical properties as well as the geometry of the microstructures within the silicon chips, so as to determine the required type of microstructure that delivers the highest energy transmission between surface and substrates, by measuring the critical heat flux of the liquid medium that is heated by the chip. The chip with the best heat transfer performance will then have its pin fin structure replicated, which can then be used in industries producing components that require high dissipation rates, such as semi-conductors in CPUs.